Strategic planning to build social trust in Technical Vocational Education Training (TVET) for indigenous youth in Kelantan, Malaysia - Azizan, Faezah Noor; Ibrahim, Asmawi; Olaitan, Ahmed Ahmed; Md Rami, Ahmad Aizuddin (Creative Publishing House, 2024)
The thrust of this study is to explore the social trust of Orang Asli youth in educational training and vocational study. Using a qualitative approach, this study was carried out in six Temiar indigenous villages in Gua Musang, Kelantan. Data were collect ed using interview techniques, focus group discussions and document analysis. A total of 32 indigenous youths were selected from six villages as study informants. The collected data was analysed using QSR NVivo software. The findings of the study show that social trust is an important element in influencing and gaining the confidence and submissiveness of Orang Asli youth towards vocational training and education. Findings also show that earning the social trust of Orang Asli youth in this training and vocational adventure is very germane to guarantee the effectiveness of this educational program. Thus, the study recommends that efforts should be intensified to improve the perception and confidence of the Orang Asli youth in educational institutions and there is a need to integrate the Orang Asli community into the decision-making process. Also, it is imperative to provide learning opportunities that are relevant to host culture and traditions along with allowing collaboration among various relevant stakeholders including the government, educational institutions and the Orang Asli community to ensure effective training and vocational education are disseminated to the Orang Asli youth.